1984
DOI: 10.1210/jcem-59-1-96
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Rates of Venous Sampling Unmask the Presence of Spontaneous, High-Frequency Pulsations of Luteinizing Hormone in Man*

Abstract: To test the validity of venous sampling rates that are generally used to characterize pulsatile LH release in man (e.g. sampling every 15-20 min), we characterized apparent LH pulse frequency in blood withdrawn variously at 20- or 4-min intervals in 19 men, at 2-min intervals in 14 men, and at 1-min intervals in 6 men. In an effort to minimize detection bias, significant LH pulses were evaluated objectively using a computerized pulse-detection algorithm, which tended to maximize recognition of true-positive LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…Spectral analysis of the deconvoluted ISR profiles confirmed the presence of two significant rhythmic components: one with a mean periodicity of 48 -96 min, the other with a mean periodicity of 6 -12 min. Altogether, these results indicate that the temporal organization of insulin secretion is analogous to that of luteinizing hormone or growth hormone, for which the presence of both rapid and slow secretory pulses has been demonstrated (20,21). Relationship with sleep and sympathovagal activity.…”
Section: Fig 1 Plasma Glucose Concentration and Isr Profiles In Onementioning
confidence: 63%
“…Spectral analysis of the deconvoluted ISR profiles confirmed the presence of two significant rhythmic components: one with a mean periodicity of 48 -96 min, the other with a mean periodicity of 6 -12 min. Altogether, these results indicate that the temporal organization of insulin secretion is analogous to that of luteinizing hormone or growth hormone, for which the presence of both rapid and slow secretory pulses has been demonstrated (20,21). Relationship with sleep and sympathovagal activity.…”
Section: Fig 1 Plasma Glucose Concentration and Isr Profiles In Onementioning
confidence: 63%
“…In the routine IGF-I assay using commercial kits, a final dilution of 1:100 is required; therefore, any error in the pipetting could generate dramatic fluctuations in the final results, which may look like a pulse. To eliminate the error of the assay, and the so-called fluctuations resulting from this, the method of Veldhuis et al (1984) was used in our pulse analysis. Merriam and Wachter (1982) suggested using the moving average procedure in the analysis, of the data to reduce noise, but this method was not used in our data analysis because it reduces the sensitivity of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Week 22 was near the beginning of the pubertal period as manifested by a prominent increase in the testosterone concentration in most of the lambs, and week 28 was the time during which IGF-I reached a plateau in the two groups. Pulses of testosterone and IGF-I were calculated according to the method described by Veldhuis et al (1984). Veldhuis et al (1984) modified the algorithm used by Merriam and Wachter (1982) and based their detection of pulses on the measurements of the hormone that exceeded the preceding local nadir by a value that was four-fold greater than the intra-assay CV of the RIA.…”
Section: Hormone Values and Pulse Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Consequently, attempts to understand any one hormone output considered alone, pling can substantially underestimate the frequency and amplitude of pulsatile activity in neurohormone eg LH, are confounded by artificial isolation of that node within a complex highly interactive servocontrol axes. [17][18][19][20][21][22] Early observations applied to LH and growth hormone (GH) release demonstrated that sampling at system. 7 In addition, a finite number of blood or other fluid samples can be obtained in clinical and animal intervals of more than 3-5 samples per hormone burst duration and half-life over at least 24 h was required experimentation, thus commonly producing short and relatively noisy (containing significant experimental to identify the majority of evident pulsatile neuroendocrine activity in the data and capture nyctohemeral uncertainty) data series that are less tractable analytically.…”
Section: Introductionmentioning
confidence: 99%